Nematodes from the Gulf of California. Part 3. Three new species of the genus Diplopeltoides Gerlach, 1962 (Nematoda: Diplopeltoididae) with overviews of the genera Diplopeltis Gerlach, 1962 and Diplopeltula Gerlach, 1950 - Holovachov, O.; Tandingan De Ley, I.; Mundo-Ocampo, M.; Gingold, R.; De Ley, P. (Russian Journal of Nematology, 2009)
Three new species, Dipfopelloides axayacatli sp. n., D. santaclarae sp. n. and D. paramasligia sp. n., are described using light microscopy. All three species are morphometrically close to D. mastigia but the fonner differs in having a hook-shaped amphid, while the latter two can be distinguished from D. masligia by having a gubernaculum with apophysis, and from each other by having, respectively, a striated cuticle (versus smooth) and a punctated interamphidial shield (versus crenate). The status and cornposition of Diplopeltoides is discussed and compared with those of Diplopeltis and Diplopeltula. The following species are transferred to different genera: Diplopeltula curta is placed in Pararaeolaimus; Diplopeltis bathmanni is placed in Diplopeilula; Diplopeltula pulcher and D. sundensis are transferred to Diplopeiloides. Three species of Diplopeltula are considered species incertae sedis: D. botula, D, striata and D, lucanica
NeMys doc_id: 17853